Qualitative study of social and healthcare educators' perceptions of their competence in education - Mikkonen K; Koskinen M; Koskinen C; Koivula M; Koskimäki M; Lähteenmäki ML; Mäki-Hakola H; Wallin O; Sjögren T; Salminen L; Sormunen M; Saaranen T; et al. (WILEY, 2022)
Competent educators are needed to ensure that social and healthcare professionals are effective and highly competent. However, there is too little evidence-based knowledge of current and required enhancements of educators' competences in this field. The aim of this study was to describe social and healthcare educators' perceptions of their competence in education. The study had a qualitative design, based on interviews with educators and rooted in critical realism. Forty-eight participants were recruited from seven universities of applied sciences and two vocational colleges in Finland, with the assistance of contact persons nominated by the institutions. The inclusion criterion for participation was employment by an educational institution as a part-time or full-time, social and/or healthcare educator. Data were collected in the period February-April 2018. The participants were interviewed in 16 focus groups with two to five participants per group. The acquired data were subjected to inductive content analysis, which yielded 506 open codes, 48 sub-categories, nine categories and one main category. The educators' competence was defined as a multidimensional construct, including categories of educators' competences in practicing as an educator, subject, ethics, pedagogy, management and organisation, innovation and development, collaboration, handling cultural and linguistic diversity, and continuous professional development. Educators recognised the need for developing competence in innovation to meet rapid changes in a competitive and increasingly global sociopolitical environment. Enhancement of adaptability to rapid changes was recognised as a necessity. The findings have social value in identifying requirements to improve social and healthcare educators' competence by helping educational leadership to improve educational standards, construct a continuous education framework and create national and/or international curricula for teacher education degree programs to enhance the quality of education. We also suggest that educational leadership needs to establish, maintain and strengthen collaborative strategies to provide effective, adaptable support systems, involving educators and students, in their working practices.